2005
DOI: 10.1111/j.1445-2197.2005.03593.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum intact parathyroid hormone as a predictor of hypocalcaemia after total thyroidectomy

Abstract: Serum PTH 1-h after total thyroidectomy is a reliable predictor of hypocalcaemia and can allow safe early discharge of patients from hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 8 publications
4
35
0
2
Order By: Relevance
“…Symptoms of serum hypocalcemia may not be manifest for up to four days after surgery and can significantly lengthen hospital stay (4,(9)(10)(11). Finding a simple and reliable method to predict which patients may show hypocalcemia could decrease patient discomfort, hospital stay and treatment costs associated with total thyroidectomy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms of serum hypocalcemia may not be manifest for up to four days after surgery and can significantly lengthen hospital stay (4,(9)(10)(11). Finding a simple and reliable method to predict which patients may show hypocalcemia could decrease patient discomfort, hospital stay and treatment costs associated with total thyroidectomy.…”
Section: Introductionmentioning
confidence: 99%
“…It is the result of parathyroid gland injury and can cause great discomfort to the patient (1,(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Symptomatic hypocalcemia is extremely unpleasant, it extends the hospitalization time (1)(2)(3)(6)(7)(8) and it increases the treatment cost. Additionally, it is a consequence of parathyroid hypofunction.…”
Section: Introductionmentioning
confidence: 99%
“…Noordzij et al 13 analyzed the pooled data from nine studies, finding that the PTH level 6 hours after surgery had the highest accuracy for predicting hypocalcemia. Based on the analysis of published Australian data, [21][22][23] The Australian Endocrine Surgeons Guidelines currently recommends the routine measurement of PTH 4 hours after total thyroidectomy to guide postoperative calcium supplementation. 24 Schlottman et al 25 suggested that the greatest sensitivity and specificity in predicting hypocalcemia are achieved when looking at the decline in PTH from baseline rather than the absolute value, demonstrating that no patient with a decrease in PTH <35% developed hypocalcemia and all patients with a decrease >80% (14% of the cohort) became hypocalcemic in a study of 106 patients.…”
Section: Discussionmentioning
confidence: 99%